COVID-19 Social Restrictions: An Opportunity to Re-visit the Concept of Harm Reduction in the Treatment of Alcohol Dependence. A Position Paper - Kouimtsidis, Christos; Pauly, Bernadette; Parkes, Tessa; Stockwell, Tim; Baldacchino, Alexander Mario (Frontiers in Psychiatry, 2021)
The COVID-19 pandemic is presenting significant challenges for health and social care systems globally. The implementation of unprecedented public health measures, alongside the augmentation of the treatment capacity for those severely affected by COVID-19, are compromising and limiting the delivery of essential care to people with severe substance use problems and, in some cases, widening extreme social inequities such as poverty and homelessness. This global pandemic is severely challenging current working practices. However, these challenges can provide a unique opportunity for a flexible and innovative learning approach, bringing certain interventions into the spotlight. Harm reduction responses are well-established evidenced approaches in the management of opioid dependence but not so well known or implemented in relation to alcohol use disorders. In this position paper, we explore the potential for expanding harm reduction approaches during the COVID-19 crisis and beyond as part of substance use treatment services. We will examine alcohol use and related vulnerabilities during COVID-19, the impact of COVID-19 on substance use services, and the potential philosophical shift in orientation to harm reduction and outline a range of alcohol harm reduction approaches. We discuss relevant aspects of the Structured Preparation for Alcohol Detoxification (SPADe) treatment model, and Managed Alcohol Programs (MAPs), as part of a continuum of harm reduction and abstinence orientated treatment for alcohol use disorders. In conclusion, while COVID-19 has dramatically reduced and limited services, the pandemic has propelled the importance of alcohol harm reduction and created new opportunities for implementation of harm reduction philosophy and approaches, including programs that incorporate the provision of alcohol as medicine as part of the substance use treatment continuum.